Effects of laser beam defocusing on high-strain-rate tensile behavior of press-hardened Zn-coated 22MnB5 steel welds. (September 2021) - Razmpoosh, M.H.; Khan, M. Shehryar; Ghatei Kalashami, A.; Macwan, A.; Biro, E.; Zhou, Y.
Highlights: Laser beam defocusing can mitigate excessive weld concavity during laser welding. The modified weld geometry improves the high strain rate performance of welds. Laser beam defocusing reverses the negative strain rate sensitivity of the welds. Abstract: Zn-based coatings have emerged as viable alternatives to the conventional Al-Si-coating for 22MnB5 press-hardening steel. However, excessive weld concavity associated with laser beam welding of Zn-coated 22MnB5 imposes an adverse effect on dynamic tensile behavior of the welds after press-hardening. In the present study, laser beam defocusing is used to mitigate excessive weld concavity during laser welding of Zn-coated 22MnB5 steel. The high-speed digital image correlation (DIC) technique during high strain rate tensile testing confirmed that the modified laser weld concavity by beam defocusing can successfully shift the failure location from the fusion zone to the base material. Laser beam defocusing reverses the negative strain rate sensitivity of the welds which drastically improves the dynamic loading performance of Zn-coated 22MnB5 laser joints in automotive crash situations.